Extracellular matrix rigidity controls podosome induction in microvascular endothelial cells. (13th December 2012) - Juin, Amélie; Planus, Emmanuelle; Guillemot, Fabien; Horakova, Petra; Albiges‐Rizo, Corinne; Génot, Elisabeth; Rosenbaum, Jean; Moreau, Violaine; Saltel, Frédéric
Abstract Background information Podosomes are actin‐based structures involved in cell adhesion, migration, invasion and extracellular matrix degradation. They have been described in large vessel endothelial cells, but nothing is known concerning microvascular endothelial cells. Here, we focussed on liver sinusoidal endothelial cells (LSECs), fenestrated microvascular cells that play major roles in liver physiology. Liver fibrosis induces a dedifferentiation of LSECs leading notably to a loss of fenestrae. Because liver fibrosis is associated with increased matrix stiffness, and because substrate stiffness is known to regulate the actin cytoskeleton, we investigated the impact of matrix rigidity on podosome structures in LSECs. Results Using primary LSECs, we demonstrated that microvascular endothelial cells are able to form constitutive podosomes. Podosome presence in LSECs was independent of cytokines such as transforming growth factor‐β or vascular endothelial growth factor, but could be modulated by matrix stiffness. As expected, LSECs lost their differentiated phenotype during cell culture, which was paralleled by a loss of podosomes. LSECs however retained the capacity to form active podosomes following detachment/reseeding or actin‐destabilising drug treatments. Finally, constitutive podosomes were also found in primary microvascular endothelial cells from other organs. Conclusions Our results show that microvascular endothelial cells are able to form podosomes without specific stimulation. Our data suggest that the major determinant of podosome induction in these cells is substrate rigidity.